Biallelic VARS variants cause developmental encephalopathy with microcephaly that is recapitulated in vars knockout zebrafish - Aleksandra Siekierska (Nature Portfolio, 2019)
tRNAs are linked with their cognate amino acid by aminoacyl tRNA synthetases (ARS). Here, the authors report a developmental encephalopathy associated with biallelic VARS variants (valyl-tRNA synthetase) that lead to loss of function, as determined by several in vitro assays and a vars knockout zebrafish model.